ANALYSIS OF PROFILE MATCHING METHOD FOR COMPUTER-BASED NATIONAL ASSESSMENT PROCTOR SELECTION DSS AT SDN 013863 SILO BONTO - andikaramdani; Adi Prijuna Lubis; Santoso (Informatika, Universitas Jenderal Soedirman, 2022)
In the implementation of a computer-based national assessment, a proctor is needed to control the assessment process so that it runs well. The selection of proctors is carried out by each educational unit, where the problem is that the selection is still done manually with unclear criteria assessment and lack of transparency in the assessment so that it is considered less than optimal. For this reason, a decision support system was created to assist each educational unit in selecting a proctor. The method used is the profile matching method, namely the profile matching method which is assessed with the assessment criteria. The research method used is a quantitative method, which is a method that uses calculations to get values ​​to determine the results of a study. Data collection techniques using interview methods, observation methods and literature study. Based on the calculation of the value in the selection of proctors with the profile matching method, it shows that the profile matching method has succeeded in obtaining the results of the assessment effectively and efficiently so that the selection of the proctor based on the highest assessment results can be carried out quickly and accurately.